La sociedad leonesa en la transición a la Edad Media - Sánchez Badiola, Juan José (Estudios humanísticos. Geografía, historia y arte, 1999)
This work tries to make some contribution to the debate about the transition process from rale Antiquity to Early Middle Ages in León.